The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1155/2019/5476909
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance of Full‐Scale Joints Composed by Concrete‐Filled Steel Tube Column and Reinforced Concrete Beam with Steel Plate‐Stud Connections

Abstract: A concrete-filled steel tube (CFST) column has the advantages of high bearing capacity, high stiffness, and good ductility, while reinforced concrete (RC) structure systems are familiar to engineers. The combinational usage of CFST and RC components is playing an important role in contemporary projects. However, existing CFST column-RC beam joints are either too complex or have insufficient stiffness at the interface, so their practical engineering application has been limited. In this study, the results of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…performed three times at each stage (Li et al, 2019). The loading process of each stage is divided into four steps: loading, unloading, reverse loading and unloading (Kanchanadevi and Ramanjaneyulu, 2018).…”
Section: Seismic Behavior Of Rc Beamsmentioning
confidence: 99%
See 1 more Smart Citation
“…performed three times at each stage (Li et al, 2019). The loading process of each stage is divided into four steps: loading, unloading, reverse loading and unloading (Kanchanadevi and Ramanjaneyulu, 2018).…”
Section: Seismic Behavior Of Rc Beamsmentioning
confidence: 99%
“…In this case, the force loading control was conducted before specimen yielded for all RC specimens. After yielded, the RC specimen was loaded to failure by displacement loading control with a displacement increment of the yield displacement Δ y , and the load was performed three times at each stage (Li et al ., 2019). The loading process of each stage is divided into four steps: loading, unloading, reverse loading and unloading (Kanchanadevi and Ramanjaneyulu, 2018).…”
Section: Experimental Programmentioning
confidence: 99%
“…Therefore, it is an excellent structure form that deserves to be promoted and studied. Nowadays, some experiments and researches on SRC structures (Chen et al, 2020) and SRC-RC column joints (Li et al, 2019) are being conducted. But, there are still few experimental and research results relevant to SRCSS column joints, especially on the shear performances in the joint core areas.…”
Section: Introductionmentioning
confidence: 99%
“…For composite joints, Li et al [28] tested the seismic performance of two kinds of CFST column-RC beam joints that are connected by vertical or U-shaped steel plates and studs and bending capacity of joints increased compared to the RC joints; Qian and Jiang [29] tested the joints consisting of reinforced concrete beams and concrete-encased CFST columns under cyclic loading, and it is observed that the energy dissipation capacity could be enhanced and the shear deformation could be decreased when the stirrup spacing reduced in the panel zones for weak joints; Liao et al [30] and Nie et al [31] pointed out that the composite joints consisting of reinforced concrete beams and concreteencased CFST columns with the outer stiffening ring also showed good hysteretic behaviour; Qian et al [32] investigated the mechanical mechanism of composite joints consisting of steel beams and concrete-encased CFST columns by validated numerical model, and it is found that the positive and negative capacities of the spatial joints under bidirectional loading were about 14% and 18% lower than those of the planar joints; additionally, Deng et al [33] experimentally studied the crack development and rigidity of joints consisting of prestressed reinforced concrete beams and concrete-encased CFST columns. Although a number of tests and analysis on composite joints with concrete-encased CFST columns have been performed, so far seismic performance and design approaches for the proposed innovative prestressed composite joints have not been reported.…”
Section: Introductionmentioning
confidence: 99%